Case report: Complete pathological admission in N3 unresectable locally advanced lung adenocarcinoma with a novel INTS10-ALK and EML4-ALK fusion after neoadjuvant crizotinib - Zhai, Xiaoqian; Wang, Ting; Lin, Yiyun; Zhang, Jiabi; Wang, Yuqing; Wang, Weiya; Zhou, Qinghua; Zhu, Daxing (Frontiers in Oncology, 2023)
Background: Although anaplastic lymphoma kinase tyrosine kinase inhibitors (ALK-TKIs) have impressive response in advanced lung adenocarcinoma with anaplastic lymphoma kinase (ALK) fusion, no guidelines points to the potential benefits of neoadjuvant ALK-TKIs for N3 unresectable locally advanced lung cancer. Current ongoing clinical trial mainly focus on the efficacy of neoadjuvant ALK-TKI in resectable locally advanced lung cancer and ignore the role of neoadjuvant ALK-TKI in N3 unresectable locally advanced lung cancer. Materials and Methods: We report a lung cancer case with a novel INTS10-ALK and EML4-ALK rearrangement achieved complete pathologic responses to neoadjuvant crizotinib. Results: Our study reported a stage IIIB-N3 lung adenocarcinoma with an unreported dual ALK rearrangement (INTS10-ALK and EML4-ALK) received 5 months of crizotinib, followed by R0 right upper lobectomy, achieving complete pathological response (ypT0 ypN0). No recurrence of tumor was found for 3 years post-operatively. Conclusion: The case supports the strategy of neoadjuvant ALK inhibitors for N3 unresectable locally advanced lung cancer may be available, expanding the spectrum of treatment of stage IIIB-N3 lung cancer.